2023
DOI: 10.1142/s0129065723500120
|View full text |Cite
|
Sign up to set email alerts
|

Six-Center Assessment of CNN-Transformer with Belief Matching Loss for Patient-Independent Seizure Detection in EEG

Abstract: Neurologists typically identify epileptic seizures from electroencephalograms (EEGs) by visual inspection. This process is often time-consuming, especially for EEG recordings that last hours or days. To expedite the process, a reliable, automated, and patient-independent seizure detector is essential. However, developing a patient-independent seizure detector is challenging as seizures exhibit diverse characteristics across patients and recording devices. In this study, we propose a patient-independent seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The Transformer architecture (Vaswani et al., 2017) has achieved success in various NLP (Devlin et al., 2018; Yang, Dai, et al., 2019; Liu, Han, et al., 2023) and image processing (Carion et al., 2020; Fan et al., 2021; Peh et al., 2022) tasks. It is particularly suitable for point cloud processing since the attention mechanism of the Transformer is invariant to the input point cloud permutation (Zhao et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Transformer architecture (Vaswani et al., 2017) has achieved success in various NLP (Devlin et al., 2018; Yang, Dai, et al., 2019; Liu, Han, et al., 2023) and image processing (Carion et al., 2020; Fan et al., 2021; Peh et al., 2022) tasks. It is particularly suitable for point cloud processing since the attention mechanism of the Transformer is invariant to the input point cloud permutation (Zhao et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…CNN-RNNs and CNN-AE architectures were similar because they both coupled CNN with RNN or AE modules to diagnose seizures [9, 33, 34, 35, 36, 37, 17, 38]. Transformer-based networks usually add a Transformer module after the CNN convolution module to improve the model’s accuracy [39, 40, 41].…”
Section: Introductionmentioning
confidence: 99%
“…We designed a TSD system to identify epilepsy seizures using pre-recorded EEG signals by short-time Fourier transform (STFT) on the most extensive publicly available EEG dataset, TUH. This paper is part of a newly formed set of papers analysing the use of Transformers on EEG signals and seizure detection to locate and detect epilepsy seizures [43, 41].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown its ability to detect seizures with an accuracy of over 90% [9,11,13,[16][17][18][19][20][21]. While these algorithms show promise, they face multiple challenges in being able to consistently detect seizures across all patients suffering from different types of seizures.…”
Section: Introductionmentioning
confidence: 99%